2018
DOI: 10.5511/plantbiotechnology.18.0402a
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of rhizobia from nodules of <i>Clitoria ternatea</i> in Thailand

Abstract: Rhizobia were isolated from the root nodules of Clitoria ternatea in Thailand. The phylogeny of the isolates was investigated using 16S rDNA and the internal transcribed spacer (ITS) region from 16S to 23S rDNA. The phylogenetic tree of the 16S rDNA showed that ten of the eleven isolates belonged to Bradyrhizobium elkanii, and one belonged to Bradyrhizobium japonicum. The topology of the ITS tree was similar to that of 16S rDNA. The acetylene reduction activity was higher for the nodules inoculated with the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…strains tested (Zaroug and Munns, 1980b). A more recent study reported the isolation and identification of 11 rhizobial strains from C. ternatea grown in Thailand (Duangkhet et al, 2018). The 16s rDNA phylogenetic analysis revealed that ten of these isolates were Bradyrhizobium elkanii strains while the remaining isolate was a Bradyrhizobium japonicum strain.…”
Section: Historical and Current Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…strains tested (Zaroug and Munns, 1980b). A more recent study reported the isolation and identification of 11 rhizobial strains from C. ternatea grown in Thailand (Duangkhet et al, 2018). The 16s rDNA phylogenetic analysis revealed that ten of these isolates were Bradyrhizobium elkanii strains while the remaining isolate was a Bradyrhizobium japonicum strain.…”
Section: Historical and Current Applicationsmentioning
confidence: 99%
“…The 16s rDNA phylogenetic analysis revealed that ten of these isolates were Bradyrhizobium elkanii strains while the remaining isolate was a Bradyrhizobium japonicum strain. These C. ternatea B. elkanii strains were shown to promote better plant growth and induce higher nitrogen-fixing capacity than B. elkanii strains isolated from soybean (Duangkhet et al, 2018).…”
Section: Historical and Current Applicationsmentioning
confidence: 99%
“…Later, nodules were washed with SDW 05 times to remove traces of hydrogen peroxide solution (if any). Nodules were subsequently crushed in 02mL SDW and stored in 1.5mL Eppendorf tubes according to sampling location (Chibeba, Kyei-Boahen, de Fátima Guimarães, Nogueira, & Hungria, 2017;Duangkhet et al, 2018;Palaniappan, Chauhan, Saravanan, Anandham, & Sa, 2010).…”
Section: Legume Nodule Preparationmentioning
confidence: 99%
“…Then nodules were treated for 1 min. in 3 % sodium hypochlorite solution and 10 times washed with sterile deionized water 22 . Disinfected nodules were transferred to a tube with 5 mL sterile deionized water and homogenized using a sterile glass rod.…”
Section: Isolation Of Diazotrophic Microorganismsmentioning
confidence: 99%